Differentiation of Neoplastic and Non-neoplastic Intracranial Enhancement Lesions Using Three-Dimensional Pseudo-Continuous Arterial Spin Labeling - Hu, Wen-zhong; Guo, Fan; Xu, Yong-qiang; Xi, Yi-bin; He, Bei; Yin, Hong; Kang, Xiao-wei (Frontiers in Neuroscience, 2022)
Background and purpose: Conventional magnetic resonance imaging(MRI) sometimes is difficult to distinguish non-neoplastic from neoplastic intra-axial enhancement lesions effectively. This study aimed to evaluate the diagnostic performance of three-dimensional pseudo-continuous Arterial Spin Labeling (3D-pCASL) to differentiate non-neoplastic from neoplastic enhancement lesions intra-axial. Materials and methods: This prospective study included thirty-five patients with high-grade gliomas (HGG), twelve patients with brain metastasis and fifteen non-neoplastic patients who underwent conventional, contrast enhancement and 3D-pCASL imaging at 3.0-T MR, all lesions were significantly enhanced.Quantitative parameters including absolute cerebral blood flow (CBF) and relative cerebral blood flow (rCBF), which were compared between neoplastic and non-neoplastic using student’s t-test. In addition, the area under the receiver-operating characteristic (ROC) curve (AUC) was performed to assess the differentiation diagnostic performance of each parameter. Results: The non-neoplastic group demonstrated significantly lower rCBF values of lesions and perilesional edema compared with neoplastic group. For the ROC analysis, both relative cerebral blood flow of lesion (rCBF-L) and relative cerebral blood flow of perilesional edema (rCBF-PE) had good diagnostic performance for discriminating non-neoplastic from neoplastic, with the AUC of 0.994 and 0.846, respectively. Conclusion: Non-contrast ASL perfusion may remarkably benefit in differentiation of non-neoplastic from neoplastic.